Historiography of life and creative work of Ya.N. Baiburtly, a notable Crimean Tatar man of letters and educator - Tair Kirimov (Крымское историческое обозрение)
he article is devoted to a brief review of the creative heritage of Yahya-Naji Baiburtly – the prominent figure of the Crimean Tatar literature and enlightener at the beginning of the 20th century. Some little-studied biographical and bibliographic materials are introduced into scientific circulation. Most of which are pre-war literary and historiographic texts, transliterated from Arabic script to Cyrillic one. The work uses memoirs of the relatives and contemporaries of Ya.N. Baiburtly, which were published by them in the national press. As a methodological basis for the research of the topic, the author used biographical, comparative typological and metacritical analysis. The theoretical basis of the research is the works of A. Krichinsky, J. Kermenchikli, Sh. Alyadinov, I. Kerimov, D. Ursu, N. Yablonovskaya, M. Khairuddinov, E. Abibullaeva. Thus, an overview of the life and literary and educational activities of Ya.N. Baiburtly helped to more clearly outline his creative personality, to determine the prospects for the aspectual study of the biography of the figure as a writer and playwright, literary translator, public figure and educator of the designated period.